Synthesis and Modification of Tetrahedron Li10.35Si1.35P1.65S12via Elemental Doping for All-Solid-State Lithium Batteries - Lin, Yuanzhong; Chen, Jian; Yan, Jiawei; Zhuang, Yanhua; Lu, Hengyi; Zhao, Chenyang (Frontiers in Chemistry, 2022)
Solid-state electrolyte (SSE), as the core component of solid-state batteries, plays a critical role in the performance of the batteries. Currently, the development of SSE is still hindered by its high price, low ionic conductivity and poor interface stability. In this work, we report the tailored synthesis of a high ionic conductive and low cost sulfide SSE for all solid-state lithium batteries. The Li10.35Si1.35P1.65S12 with favorable tetragonal structure was synthesis by increasing the concentration of Si4+, which shows an ionic conductivity of 4.28×10-3 S cm-1 and a wide electrochemical stability window up to 5V. By further modifying the composition of the electrolyte via ionic doping, the ionic conductivity of Li10.35Si1.35P1.65S12 can be further enhanced. Among them, the 1% Co4+ doped Li10.35Si1.35P1.65S12 shows the highest ionic conductivity of 6.91×10-3 S cm-1, 40% higher than the undoped one. This can be attributed to the broadened MS4- tetrahedrons and increased Li+ concentration. As a demonstration, an all-solid-state Li metal battery was assembled using TiS2 as the cathode and 1% Co4+ doped Li10.35Si1.35P1.65S12 as the electrolyte, showing capacity retention of 72% at the 110th cycle. This strategy is simple and can be easily extended for the construction of other high performance sulfide SSEs.